Oblong, a program to analyse phylogenomic data sets with millions of characters, requiring negligible amounts of RAM - Goloboff, Pablo Augusto (2013)
Oblong, a program with very low memory requirements, is presented. It is designed for parsimony analysis of data sets comprising many characters for moderate numbers of taxa (the order of up to a few hundred). The program can avoid using vast amounts of RAM by temporarily saving data to disk buffers, only parts of which are periodically read back in by the program. In this way, the entire data set is never held in RAM by the program—only small parts of it. While using disk files to store the data slows down searches, it does so only by a relatively small factor (4× to 5×), because the program minimizes the number of times the data must be accessed (i.e. read back in) during tree searches. Thus, even if the program is not designed primarily for speed, runtimes are within an order of magnitude of those of the fastest existing parsimony programs.